2002
DOI: 10.1055/s-2002-33097
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification Scores for Predicting Mortality in Coronary Artery Bypass Surgery

Abstract: All RSSs satisfactorily estimated the group risk for mortality. No RSS expressed sufficient validity to predict individuals with lethal outcome. In clinical use, CCS/Higgins proved the most practicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There were no significant differences between groups in EuroSCORE or Parsonnet indices 34 , bypass times, clamp times or volumes of administered cardioplegia (Table 3). Additional Plasma-Lyte 148 boluses did not exceed 500 ml in any patient.…”
Section: Resultsmentioning
confidence: 95%
“…There were no significant differences between groups in EuroSCORE or Parsonnet indices 34 , bypass times, clamp times or volumes of administered cardioplegia (Table 3). Additional Plasma-Lyte 148 boluses did not exceed 500 ml in any patient.…”
Section: Resultsmentioning
confidence: 95%
“…Studies applying external risk scores to centre-specific populations reported a wide range of areas under the ROC curve (0.67 [19] and 0.831 [20]). …”
Section: Discussionmentioning
confidence: 99%